Composition and Functions of the Gut Microbiome in Pediatric Obesity: Relationships with Markers of Insulin Resistance - Orsso, Camila E. (Microorganisms, 2021)
The gut microbiome is hypothesized to play a crucial role in the development of obesity and insulin resistance (IR); the pathways linking the microbiome to IR in pediatrics have yet to be precisely characterized. We aimed to determine the relationship between the gut microbiome composition and metabolic functions and IR in children with obesity. In a cross-sectional study, fecal samples from children with obesity (10–16 years old) were collected for taxonomical and functional analysis of the fecal microbiome using shotgun metagenomics. The homeostatic model assessment for insulin resistance (HOMA-IR) was determined using fasting glucose and insulin. Associations between HOMA-IR and α-diversity measures as well as metabolic pathways were evaluated using Spearman correlations; relationships between HOMA-IR and β-diversity were assessed by permutational multivariate analysis of variance. Twenty-one children (nine males; median: age = 12.0 years; BMI z-score = 2.9; HOMA-IR = 3.6) completed the study. HOMA-IR was significantly associated with measures of α-diversity but not with β-diversity. Children with higher HOMA-IR exhibited lower overall species richness, Firmicutes species richness, and overall Proteobacteria species Shannon diversity. Furthermore, HOMA-IR was inversely correlated with the abundance of pathways related to the biosynthesis of lipopolysaccharides, amino acids, and short-chain fatty acids, whereas positive correlations between HOMA-IR and the peptidoglycan biosynthesis pathways were observed. In conclusion, insulin resistance was associated with decreased microbial α-diversity measures and abundance of genes related to the metabolic pathways. Our study provides a framework for understanding the microbial alterations in pediatric obesity.